THE EFFECT OF TEACHER PEDAGOGIC COMPETENCY, TEACHER PERSONALITY, AND PARENT SOCIAL ECONOMICS ON THE LEARNING ACHIEVEMENT OF CLASS XI STUDENTS IN SMAN 2 KUPANG TIMUR KUPANG DISTRICT - Stefen Talo (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2021)
The purpose of this study was to determine the effect of teacher pedagogical competence, teacher personality competence and parents' socio-economic competence on student achievement of class XI at SMA Negeri 2 Kupang Timur. The research method is quantitative with data collection techniques carried out through the distribution of instruments and documentation. The population in the study amounted to 120 people, while the study sample amounted to 60 people who were determined by the Stratisfied Random Sampling technique. Hypothesis testing was performed using simple and multiple linear regression analysis (significance 0.05). The results of the study showed a positive and significant influence between teacher pedagogical competence on student achievement, the results of the simple regression test (F test) obtained Fcount = 2.219 (significance 0.05), Ftable 1.50. So Fcount> Ftable or 2.219> 1 , 50. There is a positive and significant effect of teacher pedagogical competence on student achievement, the results of the simple regression test (F test) obtained Fcount 1.645 (significance level 0.05), Ftable 1.50. So Fcount> Ftable or 1.645> 1.50, then there is a positive and significant influence of teacher personality competence on student achievement, the results of the simple regression test (F test) obtained Fcount 1.593 (0.05 significance), Ftable 1.50. So Fcount> Ftable or 1.593> 1.50, then there is a positive and significant influence of the socio-economic conditions of parents on student achievement. The results of the multiple regression test show that the value of Fcount = 1.998 is then consulted with the Ftable value of 1.50 (significant 0.05). old age (X3) was shown to be significant at the 95% confidence level.